Anatomy of the ankle capsule: A cadaveric study. Issue 7 (27th September 2018) - Tantigate, Direk; Noback, Peter C.; Bäcker, Henrik C.; Seetharaman, Mani; Greisberg, Justin K.; Vosseller, J. Turner
Abstract : Although bony and ligamentous injuries of the ankle are well understood, little is known about the degree to which injury of the ankle capsule can be a component of such injuries. The purpose of this study was to determine the dimensions of the ankle capsule and its relationship to adjacent structures. Thirteen fresh‐frozen ankle specimens were systematically dissected. Methylene blue solution was injected to identify the dimensions of the ankle capsule. External dimensions were measured as the distance from the capsular reflection to the bony margin of the ankle. Internal dimensions were measured as the distance from the capsular attachment of the distal tibia, fibula, and talus to the cartilage margin. The anterior aspect of the capsule demonstrated the most proximal capsular reflection in all specimens. The most proximal reflections of the anteromedial, anterior middle and anterolateral capsule were 10.3, 13.5, and 9.8 mm, respectively. The most proximal reflections of the posteromedial, posterior middle and posterolateral region were 8.7, 6.2, and 3.5 mm, respectively. There was no capsular reflection over the medial malleolus and less than 1 mm over the posterior lateral malleolus. There was a confluence of the capsule and ligamentous complex on the medial side, and also with the transverse tibiofibular ligament about the posterolateral ankle. The most proximal attachment of the ankle capsule was located at the anterior aspect of the distal tibia. The medial and posterolateral capsules were confluent with the ligamentous complexes of the ankle in those regions. Clin. Anat. 31:1018–1023, 2018. © 2018 Wiley Periodicals, Inc.